Optimization of process parameters for alkaline-catalyzed transesterification of palm oil using response surface methodology - N. Razali; H. Mootabadi; B. Salamatinia; K.T. Lee; A.Z. Abdullah (Universiti Kebangsaan Malaysia, 2010)
Biodiesel (fatty acid methyl esters) was synthesized from direct transesterification of vegetable oils, where the corresponding triglycerides react with methanol in the presence of a suitable catalyst. The alkali catalysts are the most common catalyst used in biodiesel industry, because the process proves faster and the reaction conditions are moderate compared to the acid catalyst. In the present study, biodiesel production using heterogeneous alkaline-catalysed transesterification process (KOH supported on SBA 15) was proposed. The influence of reaction temperature x1 (50 – 90 oC), ratio of methanol to oil, x2 (6:1 – 14:1 mol/mol), amount of catalyst, x3 (1 – 5wt.%), and reaction time, x4 (2 – 6 h) to the reaction was studied. These four conditions were studied using design of experiment (DOE), based on four-variable central composite design (CCD) with α = 2. The process variables were optimised using the Response Surface Methodology (RSM) in obtaining the maximum yield of biodiesel. This method was also applied to determine the significance and interaction of the variables affecting the biodiesel production. The biodiesel produced in the experiment was analysed by gas chromatography, which considered five major fatty acid methyl esters. The optimal conditions of response were found to be 70 oC for reaction temperature, 11.6 wt/wt of ratio methanol to oil, 3.91wt.% of weight of catalyst and 5 h for reaction time with 93% of biodiesel yield for predicted value and 87.3% from experimental.